2019
DOI: 10.1093/ehjcvp/pvz048
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 inhibitors in acute coronary syndrome patients with renal dysfunction: an analysis from the RENAMI and BleeMACS projects

Abstract: Aims The aim of the present study was to establish the safety and efficacy profile of prasugrel and ticagrelor in real-life acute coronary syndrome (ACS) patients with renal dysfunction. Methods and results All consecutive patients from RENAMI (REgistry of New Antiplatelets in patients with Myocardial Infarction) and BLEEMACS (Bleeding complications in a Multicenter registry of patients discharged with diagnosis of Acute Coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…In contrast, a recent registry study with 2,490 ACS patients with eGFR<60, showed significantly lower rates of death (HR 0.45, 95% CI (0.21-0.44)) and recurrent MI (HR 0.36, 95% CI (0.10-0.81) at 1-year as compared to clopidogrel 95 . Interestingly, the differences of major bleeds were not significant between DAPT treatment groups (HR 0.87, 95% CI (0.45-1.67) 95 .…”
Section: Dual Antiplatelet Treatment In Relation To Renal Functionmentioning
confidence: 74%
See 3 more Smart Citations
“…In contrast, a recent registry study with 2,490 ACS patients with eGFR<60, showed significantly lower rates of death (HR 0.45, 95% CI (0.21-0.44)) and recurrent MI (HR 0.36, 95% CI (0.10-0.81) at 1-year as compared to clopidogrel 95 . Interestingly, the differences of major bleeds were not significant between DAPT treatment groups (HR 0.87, 95% CI (0.45-1.67) 95 .…”
Section: Dual Antiplatelet Treatment In Relation To Renal Functionmentioning
confidence: 74%
“…In contrast, a recent registry study with 2,490 ACS patients with eGFR<60, showed significantly lower rates of death (HR 0.45, 95% CI (0.21-0.44)) and recurrent MI (HR 0.36, 95% CI (0.10-0.81) at 1-year as compared to clopidogrel 95 . Interestingly, the differences of major bleeds were not significant between DAPT treatment groups (HR 0.87, 95% CI (0.45-1.67) 95 . The number of patients was however small and there were no significant differences in clopidogrel versus treatment with potent P2Y12 inhibitors regarding the efficacy outcomes in the subset of patients with eGFR<30 95 .…”
Section: Dual Antiplatelet Treatment In Relation To Renal Functionmentioning
confidence: 74%
See 2 more Smart Citations
“…Finally, we did not separately analyse the different P2Y12 inhibitors. There are data suggesting that ticagrelor, a more potent P2Y12 inhibitor, reduced mortality and reinfarction in comparison with clopidogrel in patients with CKD …”
Section: Discussionmentioning
confidence: 99%